Developing Speed Reading Skills In Young Learners - Yayuk Hayulina Manurung; Sri Listiani Izar (Proceeding International Seminar of Islamic Studies, 2019)
This study is aimed to develop the speed reading skills in young learners and some issues faced along the learning. Speed reading is usually conducted in adult students and very few applied in young learners. It is considered an important goal of reading instruction. This research applied descriptive qualitative method by conducting a close observation technique where researcher acted as a non-participant observer and didn't participate and interfere to 5 subjects in teaching. The findings showed thatspeed reading strategy surprisingly could be applied in young learners. and it helps the young learners to get better result and achievement in reading This strategy is so simple, effective and easy to apply and strongly recommended to be applied in teaching young learners.